Gaijin : American prisoner of war - Faulkner, Matt (Disney/Hyperion, 2019)
After the attack on Pearl Harbor in 1941, a thirteen-year-old California boy who is half Japanese is sent to an internment camp. Story based on the history of the author's great-aunt.